Sistem literatur review: analisis kemampuan berpikir komputasi siswa dalam menyelesaikan pembelajaran matematika materi SPLDV - Nurhanurawati; Chika Rahayu; Yuli Puspita Sari (Mandalika Mathematics and Educations Journal, 2026)
This research is driven by the importance of computational thinking as a crucial foundation for students to face 21st-century challenges. Computational thinking is a logical and systematic problem-solving process that includes the ability to recognize patterns, perform decomposition, and design algorithms. In mathematics education, this ability is categorized as Higher Order Thinking Skills, which functions to simplify complex problems, specifically in the topic of Systems of Linear Equations in Two Variables. However, in reality, the computational thinking skills of students in Indonesia are still low or below the minimum mastery criteria. Therefore, this study aims to analyze the obstacles to students' computational thinking skills in solving the problems using the Systematic Literature Review method. Data were collected from scientific journal databases published within the last five to ten years. The results indicate significant obstacles in the abstraction indicator, where students fail to transform word problems into correct mathematical symbols. Additionally, in the algorithmic indicator, students are not yet able to arrange completion steps systematically. Such transformation errors at the initial stage cause the final solution to be invalid. In conclusion, a comprehensive strengthening of the computational thinking framework is essential for students to solve mathematical problems logically and structurally